MR Imaging of Cochlear Modiolus and Endolymphatic Hydrops in Patients With Menière's Disease - Sousa, Rita; Guerreiro, Carla; Eça, Tiago; Campos, Jorge; Luis, Leonel (Frontiers in Surgery, 2021)
BACKGROUND: Menière’s disease (MD) is an inner ear disorder characterized by recurrent episodes of spontaneous vertigo, unilateral low-frequency sensorineural hearing loss, tinnitus, and aural fullness. Current diagnosis still often has to rely on subjective and audiometric criteria only, although endolymphatic hydrops is recognized as the pathophysiological substrate of the disease, having been demonstrated in anatomical pathological studies and by magnetic resonance (MRI). The modiolus has close functional and anatomical relation with the cochlear nerve and membranous labyrinth and can be evaluated with MRI but no data exist on the modiolar size in MD. PURPOSE: To examine the hypothesis: Is cochlear modiolus smaller in symptomatic ears in MD? METHODS: Retrospective 3 Tesla MR study (heavily T2-weighted 3D fast asymmetric spin-echo images and 0.5mm slice thickness) comparing the mean modiolar area (MMA) in index and best ears of 8 patients with definite MD based on audiometric data. The obtained MMA values were compared against the audiometric data and the presence of vestibular endolymphatic hydrops. RESULTS: No differences were seen in MMA between best and worst ears. Ears with pure tone average (PTA) ≥25dB and more pronounced endolymphatic hydrops showed lower MMA (not statistically significant). Two patients with extreme endolymphatic hydrops showed noteworthy ipsilateral decrease in cochlear modiolus area. CONCLUSION: No differences were seen in MMA between best and worst ears in definite MD. Worse hearing function (PTA≥25dB) and more pronounced endolymphatic hydrops seems to be associated with lower MMA. This might be related with bone remodeling as a consequence of endolymphatic hydrops. Further research is needed to corroborate and explore these findings.